1994 human resource management strategic plan of the South African Department of Labour - Madzivhandila, Thiambiwi Eunice (My University, 2001)
Refer to ducument
Thesis (M. Dev.) -- University of Limpopo, 2001
Keywords: Human Resource Management; Strategic plan; South African department of Labour; Personnel management - South Africa; Strategic planning - South Africa.